St. John Chrysostom Old Testament homilies - Johannes, Chrysostomus 344-407 (Holy Cross Orthodox Press, 2003)
v. 1. Homilies on Hannah, David, and Saul -- v. 2. Homilies on Isaiah and Jeremiah -- v. 3. Homilies on the obscurity of the Old Testament. Homilies on the Psalms.